KONFLIK DALAM ORGANISASI - Tugimin Supriyadi; Adelia Ananda Putri, Noer Aini Eldi, Putri Fauziyyah, Zefanya Muri Putri Kristianti (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Conflict is one type of conflict that can cause dissatisfaction and harm organizational performance. Conflict can be divided into functional conflict and dysfunctional conflict. Functional conflict can help improve decisions and creativity, and functional conflict can cause dysfunction and harm organizational performance. There are two types of conflict, namely functional conflict which can help improve decision making and creativity, and dysfunctional conflict which can cause conflict and damage organizational performance. In this article, we will discuss types of conflict and how they can lead to conflict in organizations